Cyclosporine A but Not Corticosteroids Support Efficacy of Ex Vivo Expanded, Adoptively Transferred Human Tregs in GvHD - Landwehr-Kenzel, Sybille; Zobel, Anne; Schmitt-Knosalla, Isabela; Forke, Anne; Hoffmann, Henrike; Schmueck-Henneresse, Michael; Klopfleisch, Robert; Volk, Hans-Dieter; Reinke, Petra (Frontiers in Immunology, 2021)
Reshaping the immune balance by adoptive transfer of regulatory T-cells (Tregs) has emerged as a promising strategy to combat undesired immune reactions, including in Graft-versus-Host Disease (GvHD), which is the most lethal non-relapse complication of allogeneic hematopoietic stem cell transplantation. Currently however, little is known about the potentially inhibitory in vivo effects of conventional immunosuppressive drugs, which are routinely used to treat GvHD, on adoptively transferred Tregs. Here we demonstrate drug-specific effects of the conventional immunosuppressive drugs Cyclosporine A, Mycophenolate mofetil and methylprednisolone on adoptively transferred Tregs in a humanized NOD/SCID/IL2Rgamma-/- GvHD mouse model. The clinical course of GvHD and postmortem organ histology, including cellular organ infiltration, showed that co-administration of Cyclosporine A and Tregs is highly beneficial as it enhanced Treg accumulation at inflammatory sites like lung and liver. Similarly, co-administration of Mycophenolate mofetil and Tregs improved clinical signs of GvHD. In contrast, co-administration of methylprednisolone and Tregs resulted in reduced Treg recruitment to inflammatory sites and the fast deterioration of some animals. Consequently, when clinical trials investigating safety and efficacy of adjunctive Treg therapy in GvHD are designed, we suggest co-administering Cyclosporine A, whereas high doses of glucocorticosteroids should be avoided.